Kilka uwag o prototypowości w kontekście kognitywnych rozważań nad istotą gatunków literackich (na podstawie Trans-Atlantyku Witolda Gombrowicza) - Dobrosz-Michiewicz, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The article presents the results of research conducted in the master degree thesis, prepared at the Institute of Theory of Literature, Theatre and Audiovisual Arts, University of Lodz, under the supervision of prof. Assoc. Jarosław Płuciennik. First I present a theoretical and methodological frame of analysis of the text (especially taken form cognitive psychology of concepts: category, categorization, prototype and similarity), the second I present interpretation of terminology in relation to the concept genre and based on it doing a cognitive analysis such categories as: epic poem, heroic poetry or monk heroic poetry, based on Trans-Atlantyk by Witold Gombrowicz. The summary is an attempt to reference the conclusions derived from the analysis to the debate on the nature of the two aestethic categories – ‘style’ and ‘stylization’. These concepts are not – I suppose – immanent properties of the text, but mental constructs, first existing on mind of cognizing person. The cognitive methodology allows this aspect capture and describe.